Biomass chitosan derived cobalt/nitrogen doped carbon nanotubes for the electrocatalytic oxygen reduction reaction - Zhang, Yijie; Lu, Luhua; Zhang, Si; Lv, Zaozao; Yang, Dantong; Liu, Jinghai; Chen, Ying; Tian, Xiaocong; Jin, Hongyun; Song, Weiguo (Journal of materials chemistry. A, Materials for energy and sustainability, 2018)
Carbon nanomaterials derived from biomass are considered as important sustainable energy carriers. In this study, we report an approach to synthesize cobalt/nitrogen doped carbon nanotubes (Co-NCNTs) for high oxygen reduction reaction (ORR) activity by cobalt catalyzed carbonization of biomass chitosan. It is found that the existence of cobalt results in the transition of graphene-like carbon nanosheets to tubular graphitic carbons. Moreover, a strong chemical bonding of cobalt with nitrogen and carbon in Co-NCNTs is found, which is important for enhancing the ORR activity. The Co-NCNT catalyst under optimized synthetic conditions displays attractive ORR activity superior to those of commercial Pt/C catalysts. Furthermore, the mechanism behind the enhanced ORR activity has also been studied. This study provides a feasible synthesis approach for the scalable production of biomass derived high performance carbon based ORR catalysts. Biomass chitosan was used for the scalable synthesis of cobalt/nitrogen doped carbon nanotube composites with impressive oxygen reduction reaction activity and stability.